Modelling premature cardiac aging with induced pluripotent stem cells from a hutchinson-gilford Progeria Syndrome patient - Monnerat, Gustavo; Kasai-Brunswick, Tais Hanae; Asensi, Karina Dutra; Silva dos Santos, Danubia; Barbosa, Raiana Andrade Quintanilha; Cristina Paccola Mesquita, Fernanda; Calvancanti Albuquerque, Joao Paulo; Raphaela, Pires Ferreira; Wendt, Camila; Miranda, Kildare; Domont, Gilberto Barbosa; Nogueira, Fábio César Sousa; et al. (Frontiers in Physiology, 2022)
Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare genetic disorder that causes accelerated aging and a high risk of cardiovascular complications. However, the underlying mechanisms of cardiac complications of this syndrome are not fully understood. This study modeled HGPS using cardiomyocytes (CM) derived from induced pluripotent stem cells (iPSC) derived from a patient with HGPS and characterized the biophysical, morphological, and molecular changes found in these CM compared to CM derived from a healthy donor. Electrophysiological recordings suggest that the HGPS-CM was functional and had normal electrophysiological properties. Electron tomography showed nuclear morphology alteration, and the 3D reconstruction of electron tomography images suggests structural abnormalities in HGPS-CM mitochondria, however, there was no difference in mitochondrial content as measured by Mitotracker. Immunofluorescence indicates nuclear morphological alteration and confirms the presence of Troponin T. Telomere length was measured using qRT-PCR, and no difference was found in the CM from HGPS when compared to the control. Proteomic analysis was carried out in a high-resolution system using Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS). The proteomics data show distinct group separations and protein expression differences between HGPS and control-CM, highlighting changes in ribosomal, TCA cycle, and amino acid biosynthesis, among other modifications. Our findings show that iPSC-derived cardiomyocytes from a Progeria Syndrome patient have significant changes in mitochondrial morphology and protein expression, implying novel mechanisms underlying premature cardiac aging.